Absorptive Capabilities as Determinants of Economic Sustainability of Small and Medium-Scale Enterprises - Shodeinde, Adekunle Daniel; Nmadu, Theresa Mwuese; Olutuase, Samuel O.; Ijepe, Eleojo Anna (Business Perspective Review, 2023)
Purpose – Drawing from the Absorptive Capabilities theory, this paper examines the role played by dimensions of absorptive capabilities (i.e., knowledge acquisition, knowledge assimilation, knowledge transformation, and knowledge exploitation) on the economic sustainability of SMEs in Nigeria. Design/methodology/approach – This study uses a cross-sectional research design to collect quantitative data from 343 owners/managers of SMEs in Plateau State. Structural equation modeling through the use of the Analysis of Moments of Structures (AMOS) software, version 23 was employed to test the hypotheses. Findings – Research results indicate that all the dimensions of absorptive capabilities exert significant influence on the economic sustainability of SMEs. Thus the dimensions of absorptive capabilities serve as the antecedents of the economic sustainability of SMEs could be realized. Limitations- The focus of this study is on SMEs in Plateau State alone. The use of a cross-sectional design may also undermine the results of the study. Implications – This work adds to existing research on the subject of sustainability by revealing that dimensions of absorptive capabilities are necessary for the attainment of economic sustainability. Originality – Based on current literature, studies on the dimensions of absorptive capabilities as predictor variables are limited. No study has been conducted on the influence of absorptive capabilities using four dimensions, on the economic sustainability of SMEs. Thus it is a pioneering study in terms of both content and context.